Accelerated wound healing with a dexpanthenol-containing ointment after fractional ablative CO2 laser resurfacing of photo-damaged skin in a randomized prospective clinical trial. (3rd July 2019) - Heise, Ruth; Schmitt, Laurenz; Huth, Laura; Krings, Laura; Kluwig, David; Katsoulari, Krista-Vasiliki; Steiner, Timm; Hölzle, Frank; Baron, Jens Malte; Huth, Sebastian
Abstract: Background: Laser therapy with an ablative CO2 laser is a prominent treatment option for photo-damaged skin. The healing process and therefore the success of a laser can be supported by an appropriate postoperative treatment of the laser-treated skin. Objective : The effect of a dexpanthenol-containing ointment with petroleum jelly on wound healing after fractional ablative CO2 laser therapy of photo-damaged skin. Methods: A total of 38 patients with photo-damaged skin received fractional ablative CO2 laser treatment. Occlusive wound care was conducted for a period of 7 days. The complete wound area was divided into two sections: one that was treated with a dexpanthenol-containing ointment and a section that was treated with petroleum jelly. This study had three primary outcome measures: (1) Overview images as well as dermatoscopic images of the laser treated skin were taken immediately after laser treatment and on days 1, 2, 5 and 14 (study visits). Dermatoscopic images were analysed to determine changes of the diameter of the individual lesions between the study visits. (2) Wound-healing rate was visually assessed, based on the measure of re-epithelialization. (3) Cosmetic results were evaluated during study visits by patients and physicians applying a visual analogue scale (VAS). Results: Measuring the diameter of laser-generated lesions revealed a significantly faster cure of the lesions in wound sections that were treated with the dexpanthenol-containing ointment on days 1 and 2, in comparison to the lesions that were treated with petroleum jelly. Concordantly, visual evaluation of the wounds revealed significantly better cosmetic results and re-epithelialization on days 1, 2 and 5 after laser treatment in wound sites that were treated with the dexpanthenol-containing ointment. All patients exhibited a completed wound healing on day 14 after laser treatment. Conclusion: In this comparative study, post-operative treatment of laser-treated skin with a dexpanthenol-containing ointment led to a significantly faster wound closure in comparison to petroleum jelly, especially during the early phase of wound healing. Moreover, assessment of the cosmetic result exhibited beneficial effects of the dexpanthenol-containing ointment in the post-operative wound care after laser treatment. These results emphasize that the use of a dexpanthenol-containing ointment in the post-operative phase following CO2 laser therapy could be a promising alternative to the routinely used treatment with petroleum jelly.